O impacto da dor de dente em pré-escolares: estudo representativo de Belo Horizonte-MG - Fabiola Rocha Moura Leite (2006)
The objective of this transversal study is to verify the impact of toothache on preschooler children behavior and in their social interaction. A representative sample (n=549) of 5 years-old children were chosen from public and private schools in Belo Horizonte, Minas Gerais. The data were obtained using a questionnaire filled by the children caregivers and two different dentists performed the clinical examination. The rate of compliance for the questionnaire fill was 84%. Descriptive analysis and bivariate and multivariate logistic regression (stepwise forward procedure) were performed. The significance level was set at 0.05. The toothache prevalence was 25.1% (n=138) of which 61 (11.1%) referred that the toothache impacts on their quality of life. The most prevalent impact was stop eating some specific food (5.8%). The gender and dmf-t were the variables that were statistically significant associated with the impact of toothache. The impact of toothache on preschooler children was a negative factor in their daily activities and social interaction.